Unfair Payment Issues in Construction: Re-Thinking Alternative Payment Method For Tier-1 Contractors to Subcontractors - Swai, Laura Peter; Arewa, Andrew Oyen; Ugulu, Rex Asibuodu (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Recent statistics reveal substantial increase in late payments cases from 18% to 27%; with over £30 billion unpaid invoices to UK contractors. Furthermore, 82% of overdue invoices are monies owed to subcontractor by tier-1 main contractors. Indeed, tier-1 contractors are deemed to be the main elephant in the room despite various contractual, government and private initiatives designed to curb late payment menace. Yet, there is little research concerning use of Alternative Payment Method (APM) to leverage tier-1 contractors paying subcontractors’ invoices promptly. The aim of this study is to assess the use APM to enhance pragmatic and sustainable payment practices between tier-1 contractors and subbies. The research question is: what are the industry specific factors that influences unfair payment practices and how can alternative payment method help to leverage fair payments to subbies? The study adopted sequential exploratory design type of mixed method supported by questionnaire and structured interviews. The study population are drawn from experienced industry stakeholders including clients, contractors, designers, professionals in addition to use of computer simulation to validate proposed APM model. Initial findings reveal an optimism bias tendency of most subcontractors agreeing to lengthened and unfair payments terms induced by Tier 1 contractors. The study identified over five industry and business specific influential factors that encourages tier-1 contractors to clinch to unpropitious late payment practices. In specific terms, there are overwhelming evidences that APM has significant potential to minimize late payment in the UK construction industry if there is political, business and legislative will to implement the model.